Sampling techniques - Cochran, William Gemmell (Singapore : John Wiley & Sons (Asia) Pte, 1999)
Presents account of sampling theory as it has been developed for use in sampling surveys.
Includes bibliographical references (p. 400-411) and index.
oif 04/11/14
Loan
Keywords: Sampling (Statistics)